A docência na universidade privada: entre o trabalho e o emprego - Amorim, Eliana Aparecida de Paula Silva (2008)
This study has the main research goal of verify the heterogeneity in the practical work of teachers in the private university. My aim of research are teachers working in two private universities in São José dos Campos, the Universidade do Vale do Paraíba (UNIVAP) and the Universidade Paulista (UNIP). Among the universe of teachers of the private universities, it was chosen teachers of undergraduate courses of law, management and pedagogy. From this data and analysis of interviews with teachers, I tried to put in evidence not the actor himself but how the teacher s work is influenced by the institution where it is done. To accomplish this task I employ contributions of authors such as Brandão, Wanderley, Trindade and Cunha, that work with university development as a whole, without forget classical authors as Marx and Arendt, for theoretical basis I also discuss the contributions of researchers as Sampaio and Anastasiou and Pimenta, with emphasis the undergraduate private teaching and teaching skill in high level teaching respectively